2009
DOI: 10.1002/jhet.130
|View full text |Cite
|
Sign up to set email alerts
|

Self termination of ring opening reaction of p‐substituted phenol‐based benzoxazines: An obstructive effect via intramolecular hydrogen bond

Abstract: in Wiley InterScience (www.interscience.wiley.com).The ring opening polymerizations of p-substituted phenol-based benzoxazines are self-terminated as soon as dimers form. The polymerization of benzoxazine monomers does not proceed according to the theoretical mechanism even though the conditions, temperature, molar ratio, solvent polarity, and reactant ratio are varied. The speculated mechanism, involving the unique structure of a dimer with interand intramolecular hydrogen bonds, is applied to explain an obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 13 publications
(28 reference statements)
3
46
0
Order By: Relevance
“…Moreover, many studies about the effects of different 24 reactant structures [13,16,[19][20][21][22], reactant ratios [23,24], reaction 25 temperatures [15], solvent effect [25], and reaction duration [22] 26 have also been reported; results showed that these conditions can 27 influence benzoxazine yield and generate various byproducts. 28 Many studies have focused on synthesizing novel benzoxazine 29 monomers [26][27][28].…”
Section: Q2mentioning
confidence: 98%
“…Moreover, many studies about the effects of different 24 reactant structures [13,16,[19][20][21][22], reactant ratios [23,24], reaction 25 temperatures [15], solvent effect [25], and reaction duration [22] 26 have also been reported; results showed that these conditions can 27 influence benzoxazine yield and generate various byproducts. 28 Many studies have focused on synthesizing novel benzoxazine 29 monomers [26][27][28].…”
Section: Q2mentioning
confidence: 98%
“…Although these types of polymerization reactions are presented, Chirachanchai et al [40] stated that the polymerization of benzoxazine monomers does not proceed according to the theoretical mechanism even though the conditions, temperature, molar ratio, solvent polarity, and reactant ratio are varied. Obstructive effects on ringopening polymerization leading to unique structure of a dimer ( Figure 10) with inter-and intramolecular hydrogen bonds are leading to yet another speculated mechanism.…”
Section: Tg Studies: Thermal Stability Of Polybenzoxazinesmentioning
confidence: 99%
“…A detailed investigation [40] carried out allows one to conclude that the ring opening of p-substituted phenols provide neither linear oligomers nor polymers, but only dimers (Figures 10 and 11). …”
Section: Tg Studies: Thermal Stability Of Polybenzoxazinesmentioning
confidence: 99%
“…The explanation for this observation is as follows: previous studies showed that polymerization of p-substituted phenol-based benzoxazines did not produce a linear polymer but only dimer, owing to the strong intramolecular hydrogen bond between the hydroxyl and nitrogen atom of the Mannich bridge which obstructed the polymerization. [13,14] As far as PC-a composites, the coordination interaction between lanthanum ion (or the other ions) and nitrogen atom destroys the OH . .…”
Section: Gpc Analysismentioning
confidence: 99%